2020
DOI: 10.3390/md18090437
|View full text |Cite
|
Sign up to set email alerts
|

The Microbial Community Associated with Rhizostoma pulmo: Ecological Significance and Potential Consequences for Marine Organisms and Human Health

Abstract: Jellyfish blooms are frequent and widespread in coastal areas worldwide, often associated with significant ecological and socio-economic consequences. Recent studies have also suggested cnidarian jellyfish may act as vectors of bacterial pathogens. The scyphomedusa Rhizostoma pulmo is an outbreak-forming jellyfish widely occurring across the Mediterranean basin. Using combination of culture-based approaches and a high-throughput amplicon sequencing (HTS), and based on available knowledge on a warm-affinity jel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 163 publications
(241 reference statements)
2
24
0
Order By: Relevance
“…The A. coerulea -associated bacterial communities were dominated by Vibrio , as has previously been shown for the communities associated with A. aurita ( Weiland-Bräuer et al, 2015 ; Kramar et al, 2019 ; Jaspers et al, 2020 ). The bacterial communities associated with N. nomurai and R. esculentum (family Rhizostomatidae) were similarly dominated by a single genus, Mycoplasma , which was consistent with previous results for R. pulmo (family Rhizostomatidae) ( Basso et al, 2019 ; Stabili et al, 2020 ). Interestingly, three bacterial genera presented relatively similar abundances associated with C. nozakii including Shingomonas , Phyllobacterium , and Ralstonia .…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The A. coerulea -associated bacterial communities were dominated by Vibrio , as has previously been shown for the communities associated with A. aurita ( Weiland-Bräuer et al, 2015 ; Kramar et al, 2019 ; Jaspers et al, 2020 ). The bacterial communities associated with N. nomurai and R. esculentum (family Rhizostomatidae) were similarly dominated by a single genus, Mycoplasma , which was consistent with previous results for R. pulmo (family Rhizostomatidae) ( Basso et al, 2019 ; Stabili et al, 2020 ). Interestingly, three bacterial genera presented relatively similar abundances associated with C. nozakii including Shingomonas , Phyllobacterium , and Ralstonia .…”
Section: Discussionsupporting
confidence: 91%
“…Several studies found Mycoplasma to be the prevailing taxa in the microbiomes of the scyphozoans A. aurita (Weiland-Bräuer et al, 2015;Daley et al, 2016;Jaspers et al, 2020), and R. pulmo (Basso et al, 2019;Stabili et al, 2020), similar to the present study. Vibrio has previously been found to be the dominant genus in A. aurita (Weiland-Bräuer et al, 2015;Kramar et al, 2019;Jaspers et al, 2020), A. coerulea (Chen et al, 2020), R. pulmo (Basso et al, 2019;Stabili et al, 2020), Cotylorhiza tuberculata (Cortés-Lara et al, 2015), C. lamarckii (Schuett and Doepke, 2010), and C. capillata (Schuett and Doepke, 2010;Clinton et al, 2020), and was abundant in A. coerulea, N. nomurai and R. esculentum in this study. Genus Tenacibaculum was dominant in N. nomurai and R. esculentum in this study, and has been suggested as a key part of the bacterial communities of A. aurita (Jaspers et al, 2020), C. tuberculata (Cortés-Lara et al, 2015;Viver et al, 2017) and P. noctiluca (Delannoy et al, 2011).…”
Section: The Composition and Potential Functions Of The Bacterial Communities Associated With The Four Scyphozoanssupporting
confidence: 91%
See 2 more Smart Citations
“…These bacteria, due to their capability to synthesize antimicrobial compounds when attached to live or inert surfaces, were previously recognized as significant players in the host defense towards pathogens and fouling organisms from the surrounding environment. Rhizostoma pulmo-associated microbiota were investigated in three distinct compartments, namely umbrella, oral arms, and the mucus secretion [47,48]. Actinobacteria, Bacteroidetes, Chlamydiae, Cyanobacteria, Deinococcus-Thermus, Firmicutes, Fusobacteria, Planctomycetes, Proteobacteria, Rhodothermaeota, Spirochaetes, Tenericutes, and Thaumarchaeota were the phyla isolated from all the three R. pulmo compartments in the sampling times.…”
Section: Interaction With Microbial Communitiesmentioning
confidence: 99%